2023
DOI: 10.3389/fpsyg.2023.1048164
|View full text |Cite
|
Sign up to set email alerts
|

Association of relative deprivation with loneliness and its underlying mechanisms: Evidence from Chinese migrant children

Abstract: Given the increase in the number of internal migrant children, the mental health problems (e.g., loneliness) of this population have received widespread attention. Relative deprivation is considered to be related to migrant children’s loneliness. However, the underlying mechanisms of this relationship remain unclear. Therefore, the present study tested the possible mediating role of self-esteem and the moderating role of belief in a just world in the association between relative deprivation and loneliness of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 155 publications
0
3
0
Order By: Relevance
“…According to the worldview verification model, worldviews help individuals to appraise and respond to negative life experiences (Major et al, 2007). When the actual situation or their experience is inconsistent with the worldview, adolescents' sense of certainty and security decreases, which is harmful for their adaptive emotional and behavioral development (Xiong & Xu, 2023). In this vein, high‐SDO adolescents view the world as a “competitive jungle” (Duckitt et al, 2002), may be more tolerant to aggression, and likely to engage in aggressive behavior to achieve their goals (Goodboy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the worldview verification model, worldviews help individuals to appraise and respond to negative life experiences (Major et al, 2007). When the actual situation or their experience is inconsistent with the worldview, adolescents' sense of certainty and security decreases, which is harmful for their adaptive emotional and behavioral development (Xiong & Xu, 2023). In this vein, high‐SDO adolescents view the world as a “competitive jungle” (Duckitt et al, 2002), may be more tolerant to aggression, and likely to engage in aggressive behavior to achieve their goals (Goodboy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…That is, when experiencing peer victimization, adolescents low in SDO are more likely to have high levels of anger rumination, which further increases the risk of Internet addiction. To date, no published studies have directly examined the moderating role of SDO in the association between peer victimization, anger rumination and Internet addiction; however, the related research has provided further evidence of this possible mechanism (e.g., Wu et al, 2014; Xiong & Xu, 2023). For instance, one study based on migrant children found that high belief in a just world exacerbated the negative effect of relative deprivation on loneliness (Xiong & Xu, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation